BODY COMPOSITION AND PHYSICAL FITNESS OF ADOLESCENTS OF DIFFERENT SOCIAL AND ECONOMICAL LEVEL (Fiep Bulletin - online, 2014)
The analysis of physical changes occurred during the process of growth and development, such as the physical fitness conditions, is so important for to detect and prevent the no health development of the adolescents and children. Thus, the aim of this study was analyze the body composition and physical fitness of 76 adolescents (10-15 years), considering the biological maturation and the social and economical level. The body composition was estimated through the measurements of skinfolds thickness, body perimeters, bone diameters, height and total body mass. These measurements permitted estimate the parameters: relative body mass, fat mass, residual mass, bone mass, and muscle mass. The body mass index and the somatotype and its respective classifications were obtained. Physical fitness testing were applied to establish the comparison between the groups: flamingo balance, tapping test of arms, sit and reach, standing broad jump, hand grip test, abdominal test, bent arm hang, velocity shuttle run and endurance shuttle run. The biological maturation was estimated by the presence or absence of menarche, and the social and economical level was done by the discrimination of school (public or private). The comparison between the groups was done by the t-Student test non pareated (p = 0.05). The results obtained in the present study show that the social and economical level wasn't determinant factor of significant differences between the studied adolescents.
Keywords: adolescents; body composition; biological development